Ice formation in the subcooled brine environment. (April 2016) - Yun, Xiao; Brooks, Sam; Cheng, Yan; Hales, Alastair; Lucas, Edward; McBryde, Dan; Quarini, Giuseppe
Highlights: Ice can be generated in the subcooled brine, a miscible fluid with water. Injection position, flow rheology, brine temperature and concentration are studied. The experimental work proposes a new method of ice production mechanism. Higher COP is expected than a scraped surface ice maker. Abstract: Generating ice in a fluid immiscible with water is relatively easy but considerably more difficult if the chosen fluid is hydrophilic. Our experimental work showed that, ice can be produced when water is introduced to a bath of subcooled brine and it was believed that, the rate of heat transfer between the two fluids needs to be higher than that of mass transfer to allow the formation of ice to occur as a result. Flow rheology, hence the size of the active surface area of the injected water stream, brine temperature and concentration are the key factors influencing how much ice can be made in the process. Conversion ratios of two ice collection methods are compared over a range of brine temperatures and concentrations. The washing method (wet collection) was found to collect up to 27% more ice than dry collection. Washing is also very effective in rinsing off the brine and salt on the ice's surface and the bulk salinity would drop from 13% to 1%. Since the evaporator temperature has to be higher than the eutectic point of brine, it was suggested that, the coefficient of performance, COP, will be very promising. In addition, this way of ice production should achieve higher efficiency than a scraped surface ice maker and it is simpler in that it requires no complex mechanical harvesting equipment, and with the vast liquid–liquid surface areas possible, promises to be able to produce high quantities of ice per unit volume of equipment.